2008
DOI: 10.1080/00140130701617025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pace and stress on upper extremity kinematic responses in sign language interpreters

Abstract: Sign language interpreters suffer from high levels of upper extremity disorders and burnout due to the physical and cognitive demands of interpreting. The objective of this research was to quantify the wrist kinematics of interpreting and to assess how speaker pace and psychosocial stress influence wrist kinematics. Professional interpreters interpreted a pre-recorded lecture, while the speaking pace of the lecture varied. One group of subjects was exposed to environmental conditions intended to induce stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
1
15
1
3
Order By: Relevance
“…V mean for each trial was calculated as the mean of the absolute value of the time-series joint angular velocity data (Marras & Schoenmarklin, 1993;Qin et al, 2008) from each 15-minute interpreting sample. In addition, time series of joint angular velocity data were also used to assess the number of MBs, which was used to determine MB time .…”
Section: Data Analysis and Extraction Of Dependent Measuresmentioning
confidence: 99%
See 4 more Smart Citations
“…V mean for each trial was calculated as the mean of the absolute value of the time-series joint angular velocity data (Marras & Schoenmarklin, 1993;Qin et al, 2008) from each 15-minute interpreting sample. In addition, time series of joint angular velocity data were also used to assess the number of MBs, which was used to determine MB time .…”
Section: Data Analysis and Extraction Of Dependent Measuresmentioning
confidence: 99%
“…Previous research has reported mean angular velocities of 53-84 /s and 28-47 /s about the flexion/extension and radial/ulnar deviation axis of the wrist on the dominant hand during signing (Delisle et al, 2005;Qin et al, 2008). While these ranges are large, the consistency in mean velocities between studies is important.…”
mentioning
confidence: 93%
See 3 more Smart Citations